Characterization of Bacillus anthracis Spore Proteins Using a Nanoscaffold Vaccine Platform - Weilhammer, Dina R.; Dunkle, Alexis D.; Boone, Tyler; Gilmore, Sean F.; Khemmani, Mark; Peters, Sandra K. G.; Hoeprich, Paul D.; Fischer, Nicholas O.; Blanchette, Craig D.; Driks, Adam; Rasley, Amy (Frontiers in Immunology, 2020)
Subunit vaccines are theoretically safe and easy to manufacture but require effective adjuvants and delivery systems to yield protective immunity, particularly at critical mucosal sites such as the lung. We investigated nanolipoprotein particles (NLPs) containing the Toll-like receptor 4 agonist monophosphoryl lipid A (MPLA) as a platform for intranasal vaccination against Bacillus anthracis. Modified lipids enabled attachment of disparate spore and toxin protein antigens. Intranasal vaccination of mice with B. anthracis antigen-MPLA-NLP constructs induced robust IgG and IgA responses in serum and in bronchoalveolar and nasal lavage. Typically, a single dose sufficed to induce sustained antibody titers over time. When multiple immunizations were required for sustained titers, specific antibodies were detected earlier in the boost schedule with MPLA-NLP-mediated delivery than with free MPLA. Administering combinations of constructs induced responses to multiple antigens, indicating potential for a multivalent vaccine preparation. No off-target responses to the NLP scaffold protein were detected. In summary, the NLP platform enhances humoral and mucosal responses to intranasal immunization, indicating promise for NLPs as a flexible, robust vaccine platform against B. anthracis and potentially other inhalational pathogens.